Multilayer composite drug-loaded nano motor and preparation method and application thereof

By designing a drug-loading nanomotor with multi-layer composite structure, using the spiny structure of Xanthium structure to anchor the thrombus, and responsively release the drug through ROS, the targeting and enrichment of existing drug-loading nanoparticles in the treatment of thrombus is solved. The problem of low rate has achieved precise treatment of thrombosis.

CN119455020APending Publication Date: 2025-02-18NANJING DRUM TOWER HOSPITAL
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411722794.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

Existing drug-loaded nanoparticles are difficult to overcome blood flow resistance when treating thrombosis, and have low targeting and enrichment rates, resulting in poor treatment results.

Method used

The drug-loaded nanomotor adopts a multi-layer composite structure, through the design of a moxa xanthium structure, uses a spiny structure to anchor the thrombus site, and achieves precise treatment through ROS-responsive drug release.

Benefits of technology

It improves the targeting and enrichment rate of drug-loaded nanoparticles, realizes precise treatment of thrombosis, and has the advantages of good tissue specificity and strong practicality.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119455020A_ABST
    Figure CN119455020A_ABST
Patent Text Reader

Abstract

The invention discloses a multi-layer composite drug-loading nano motor and a preparation method and application thereof, the drug-loading nano motor has a multi-layer composite structure and a xanthium-like appearance, and is prepared by a layer-by-layer wrapping method. Due to the multi-layer composite structure, the nano-particles can target a lesion area through physical adsorption, meanwhile, the 'Xanthium sibiricum' spike can anchor a focus and release medicine in a responsive mode, and therefore precise treatment on complex diseases is achieved. The preparation method provided by the invention has the advantages of simplicity in operation, high universality, convenience in large-scale production and the like, and the prepared nanoparticles can overcome blood flow resistance, target a focus area and locally release drugs, and have potential application prospects and practical significance in the biomedical fields of tissue repair, focus ablation and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of biomedical materials, and specifically relates to a multilayer composite drug-loaded nanomotor and a preparation method and application thereof. Background Art

[0002] Thrombus is a blood clot that forms in the lumen of arteries and / or veins, restricts blood flow and causes clinical symptoms. Its formation is closely related to many cardiovascular diseases, including deep vein thrombosis, pulmonary embolism, ischemic stroke and myocardial infarction. Despite this, the effective treatment rate of thrombosis is still at a low level. The reason is that the current classic thrombolytic drug therapy is affected by a narrow therapeutic window, poor thrombolytic effect, severe bleeding risk and high recurrence rate. Therefore, the construction of drug-loaded nanoparticles with targeted effects to achieve precise treatment of thrombosis has become a general trend in recent years.

[0003] Although nanoparticle targeted drug delivery technology has improved the drug delivery efficiency to a certain extent, it is difficult to overcome the influence of blood flow resistance, and the lesion retention rate is low and the penetration is poor, which greatly limits the treatment effect. Summary of the invention

[0004] Purpose of the invention: The technical problem to be solved by the present invention is to provide a drug-loaded nanomotor with a Xanthium-like structure in view of the shortcomings of the prior art, so as to enhance the precise targeting and autonomous anchoring capabilities of the drug-loaded nanomotor.

[0005] In order to achieve the above object, the technical solution adopted by the present invention is as follows: A method for preparing a multilayer composite drug-loaded nanomotor comprises the following steps: S1. Add anhydrous ferric chloride, sodium acetate, poly(4-styrenesulfonic acid-co-maleic acid) sodium salt, L-ascorbic acid and deionized water to ethylene glycol, stir evenly to obtain a mixed aqueous solution, then add sodium hydroxide to the mixed aqueous solution, stir to obtain a yellow-brown mixture; add the yellow-brown mixture to a high-pressure reactor, obtain a precipitate through a hydrothermal reaction, and repeatedly wash with ethanol and deionized water to obtain pure Fe3O4 particles; S2, mixing the Fe3O4 nanoparticles prepared in S1 with ammonia water and ethanol, stirring and reacting at 50-60°C, adding a surface modifier in the middle, collecting the mixed solution after the reaction after 30-60 min, and washing it with water and ethanol in turn to obtain Fe3O4@SiO2 composite particles; S3, the Fe3O4@SiO2 composite particles prepared in S2 and a mixed solution of copper nitrate are subjected to a hydrothermal synthesis method to obtain Fe3O4@CuSiO3 composite particles with a thorny structure; S4. The Fe3O4@CuSiO3 composite particles prepared in S3 are amino-modified under the action of 3-aminopropyltriethoxysilane, and then connected with boronic acid bonds under the action of 4-(bromomethyl)phenylboronic acid; then rt-PA solution is added and allowed to stand to obtain rtpa / Fe3O4@CuSiO3 loaded with thrombolytic drugs.

[0006] Wherein, in step S1, the usage ratio of anhydrous ferric chloride, sodium acetate, poly(4-styrenesulfonic acid-co-maleic acid) sodium salt, L-ascorbic acid, deionized water and ethylene glycol is (0.24~0.30g):(1.1~1.3g):(0.2~0.5g):(0.001~0.005g):(20~40μL):(14~18mL), preferably 0.26g:1.2 g:0.4 g:0.004 g,:30 μL:16mL.

[0007] Preferably, the mass ratio of the mixed aqueous solution to sodium hydroxide is (1-1.5):(8-8.2).

[0008] Preferably, in step S1, the temperature of the hydrothermal reaction is 190-210° C., and the reaction time is 9-12 h.

[0009] Preferably, in step S2, the dosage ratio of the Fe3O4 nanoparticles to ammonia water and ethanol is (3-5):1:(15-22).

[0010] Preferably, in step S2, the surface modifier is tetraethyl orthosilicate, and the mass ratio of tetraethyl orthosilicate to Fe3O4 nanoparticles is (100-120):(22-27); the tetraethyl orthosilicate is added by stirring for 10-30 min and then adding half of the tetraethyl orthosilicate, and then adding the other half of the tetraethyl orthosilicate again after an interval of 30-45 min.

[0011] Preferably, in step S3, the copper nitrate mixed solution comprises copper nitrate, deionized water and ammonia water, wherein the usage ratio of copper nitrate, deionized water and ammonia water is (100-110): (43100-43200): (790-800); the temperature of hydrothermal synthesis is 130-160°C, and the reaction time is 12-14 h.

[0012] Preferably, in step S4, the 3-aminopropyltriethoxysilane used is prepared using an ethanol solution, and the 4-(bromomethyl)phenylboronic acid used is prepared using a methanol solution; in the obtained rtpa / Fe3O4@CuSiO3, the drug loading amount of rt-PA is 10~20 wt.%, preferably 14 wt.%.

[0013] Furthermore, the multilayer composite drug-loaded nanomotor prepared by the above preparation method is also within the protection scope of the present invention.

[0014] Furthermore, the present invention also claims to protect the use of the above-mentioned multi-layer composite drug-loaded nanomotor in the preparation of drugs for treating arterial thrombosis. Beneficial Effects

[0015] (1) The nanocarrier of the present invention has a multilayer structure, a multilayer composite structure and a "Xanthium-like" appearance, and is prepared by a layer-by-layer wrapping method. The multilayer composite structure enables the nanoparticles to target the lesion area by physical adsorption. At the same time, the "Xanthium-like" spikes can anchor the lesion and release drugs responsively. The thrombus site can be targeted by physical manipulation, thereby achieving precision treatment for complex diseases. It has the advantages of good tissue specificity and strong practicality. The multilayer composite drug-loaded nanomotor can anchor the thrombus site with the help of the multi-thorny structure, so that it can play a role in the complex blood flow environment, and can be used for drug delivery of various blood system diseases.

[0016] (2) The present invention adopts a ROS-responsive drug release method with strong tissue specificity, thereby avoiding drug leakage during transportation.

[0017] (3) The present invention uses a hydrothermal synthesis method to prepare multilayer composite drug-loaded nanomotors. The method is simple, easy to operate, low-cost, and does not require high technical requirements. The prepared multilayer composite drug-loaded nanomotors have the ability of precise targeting and autonomous anchoring. They can reach the thrombus site through magnetic attraction, achieve lesion enrichment by imitating the thorn-like structure of Xanthium sibiricum, and release thrombolytic drugs in a ROS-responsive manner. Compared with traditional drug-loaded nanoparticles, they have better targeting, enrichment rate, and precision. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] The present invention will be further described in detail below in conjunction with the accompanying drawings and specific embodiments, and the above and / or other advantages of the present invention will become more clear.

[0019] Figure 1 These are electron microscope images of the products obtained in each step of Example 1, wherein Figure A is an electron microscope image of Fe3O4, Figure B is an electron microscope image of Fe3O4@SiO2, and Figure C is an electron microscope image of Fe3O4@CuSiO3.

[0020] Figure 2 This is an electron microscope image of the multilayer composite drug-loaded nanomotor prepared in Example 2.

[0021] Figure 3 This is the in vivo imaging image of mice in Example 4.

[0022] Figure 4This is a diagram showing the evaluation of thrombus area in mice after treatment of acute arterial thrombosis with multilayered drug-loaded nanomotors. DETAILED DESCRIPTION

[0023] The present invention can be better understood with reference to the following examples.

[0024] The preparation method of the multilayer composite drug-loaded nanomotor of the present invention comprises the following steps: S1, Fe 3+ The mixed salt solution and the precipitant are added to ethylene glycol, and stirred to obtain a mixed aqueous solution, and then hydrogen peroxide is added to the mixed aqueous solution, and stirred to obtain a yellow-brown mixture; the yellow-brown mixture is added to a high-pressure reactor, and a precipitate is obtained through a hydrothermal reaction, and the precipitate is repeatedly washed with ethanol and deionized water to obtain pure Fe3O4 particles; S2, mixing the Fe3O4 nanoparticles prepared in S1 with ammonia water and ethanol, stirring and reacting at 50°C, adding a surface modifier in the middle, collecting the mixed solution after the reaction after 30 minutes, and washing it with water and ethanol in turn to obtain Fe3O4@SiO2 composite particles; S3, the Fe3O4@SiO2 composite particles prepared in S2 and a mixed solution of copper nitrate are subjected to a hydrothermal synthesis method to obtain Fe3O4@CuSiO3 composite particles with a thorny structure; S4. The Fe3O4@CuSiO3 composite particles prepared in S3 are amino-modified under the action of 3-aminopropyltriethoxysilane, and then connected with boronic acid bonds under the action of 4-(bromomethyl)phenylboronic acid; then rt-PA solution is added and allowed to stand to obtain rtpa / Fe3O4@CuSiO3 loaded with thrombolytic drugs.

[0025] Example 1 Preparation of Fe3O4@SiO2 particles Add 0.26g FeCl3, 1.2g NaAc, 0.4g PSSMA, 0.004g vitamin C, and 30μL deionized water to 16ml ethylene glycol, mix thoroughly to dissolve to obtain a brown solution. Continue to add 0.24g NaOH, stir and dissolve to obtain a yellow-black solution. Transfer the liquid to an autoclave, put it into a muffle furnace, and react at 190℃ for 9h. After the reaction, the mixed solution is rinsed with water and ethanol in turn to obtain Fe3O4 particles.

[0026] Add water to the obtained Fe3O4 particles to 12mL, mix with 80mL ethanol and 4mL ammonia water, and transfer to a three-necked flask. Heat the flask in a 50℃ water bath and stir with a 600r electric stirrer. After stirring for 10min, add a drop of tetraethyl orthosilicate every 20s, with a total of 400μL. After stirring for 30min, add 400μL of tetraethyl orthosilicate again. After 30min, collect the mixed solution after the reaction, wash it with water and ethanol in turn, and obtain Fe3O4@SiO2 particles.

[0027] Example 2 Preparation of Fe3O4@CuSiO3 thorn-like particles 0.0216g of copper nitrate trihydrate was added to 8.64ml of water, and then 0.16ml of ammonia water and 0.0208g of Fe3O4@SiO2 were added. After ultrasonic mixing, the mixture was put into a reactor and reacted at 140℃ for 12h. After being placed at room temperature, the reactants were taken out and washed with water and ethanol to obtain Fe3O4@CuSiO3 particles with thorny structure.

[0028] Figure 1 Figure 1 is an electron microscope image of the products obtained in each step of this embodiment, wherein Figure A is an electron microscope image of Fe3O4, Figure B is an electron microscope image of Fe3O4@SiO2, and Figure C is an electron microscope image of Fe3O4@CuSiO3. It can be seen that the nanoparticles have good monodispersity during the synthesis process, and finally form thorn-shaped nanoparticles with ferroferric oxide as the core and copper silicate ions deposited on the surface.

[0029] Example 3 Preparation of multilayer composite drug-loaded nanomotors 20 mg Fe3O4@CuSiO3 was amino-modified under the action of 200 ul APTES for 24 hours, washed twice with alcohol, and then treated with 200 mg PBA for 24 hours, and washed twice with deionized water. The rt-PA solution was mixed evenly with the above-treated nanoparticles, and allowed to stand at room temperature for 30 minutes. The excess rt-PA was removed by magnetic attraction to obtain a multilayer composite drug-loaded nanomotor. Figure 2 This is an electron microscope image of the multilayer composite drug-loaded nanomotor prepared in this example, indicating that after the protein drug is loaded on the surface, the nanoparticles still retain a relatively complete thorn-like appearance.

[0030] Example 4 Application of multilayer composite drug-loaded nanomotor in the preparation of drugs for treating arterial thrombosis The carotid arteries of 6-7 week old C57BL / 6J mice were treated with filter paper soaked in 10% FeCl3 for 5 min to induce arterial thrombosis. A 0.5T magnet was used to attract the nanomotors to the thrombus site, and the Cy5.5 fluorescence signals were recorded by video acquisition software at 0, 15, 30, 45, and 60 min after injection, as shown in Figure 2. Figure 3As shown in Figure 2, fluorescence imaging proves that the nanomotor can effectively anchor the thrombus area. One hour after thrombus formation, mice were injected with multilayer composite drug-loaded nanomotor (drug loading equivalent to 0.5 mg / kg free drug). After 3 days of treatment, Figure 4 As shown, the thrombus volume can be reduced to 21% after treatment with drug-loaded nanomotors. The multilayer composite drug-loaded nanomotors have a significant effect on the treatment of arterial thrombosis. This strategy can be widely used in the field of precision treatment.

[0031] The present invention provides a multilayer composite drug-loaded nanomotor and its preparation method and application ideas and methods. There are many methods and ways to implement the technical solution. The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the protection scope of the present invention. All components not specified in this embodiment can be implemented by existing technologies.

Claims

1. A method for preparing a multilayer composite drug-loaded nanomotor, characterized in that: The steps include: S1. Add anhydrous ferric chloride, sodium acetate, poly(4-styrenesulfonic acid-co-maleic acid) sodium salt, L-ascorbic acid and deionized water to ethylene glycol, stir evenly to obtain a mixed aqueous solution, then add sodium hydroxide to the mixed aqueous solution, stir to obtain a yellow-brown mixture; add the yellow-brown mixture to a high-pressure reactor, obtain a precipitate through a hydrothermal reaction, and repeatedly wash with ethanol and deionized water to obtain pure Fe3O4 particles; S2, mixing the Fe3O4 nanoparticles prepared in S1 with ammonia water and ethanol, stirring and reacting at 50-60°C, adding a surface modifier in the middle, collecting the mixed solution after the reaction after 30-60 min, and washing it with water and ethanol in turn to obtain Fe3O4@SiO2 composite particles; S3, the Fe3O4@SiO2 composite particles prepared in S2 and a mixed solution of copper nitrate are subjected to a hydrothermal synthesis method to obtain Fe3O4@CuSiO3 composite particles with a thorny structure; S4. The Fe3O4@CuSiO3 composite particles prepared in S3 are amino-modified under the action of 3-aminopropyltriethoxysilane, and then connected with boronic acid bonds under the action of 4-(bromomethyl)phenylboronic acid; then rt-PA solution is added and allowed to stand to obtain rtpa / Fe3O4@CuSiO3 loaded with thrombolytic drugs.

2. The method for preparing a multilayer composite drug-loaded nanomotor according to claim 1, characterized in that: In step S1, the usage ratio of anhydrous ferric chloride, sodium acetate, poly(4-styrenesulfonic acid-co-maleic acid) sodium salt, L-ascorbic acid, deionized water and ethylene glycol is (0.24-0.30 g): (1.1-1.3 g): (0.2-0.5 g): (0.001-0.005 g): (20-40 μL): (14-18 mL).

3. The method for preparing a multilayer composite drug-loaded nanomotor according to claim 1, characterized in that: In step S1, the mass ratio of the mixed aqueous solution to sodium hydroxide is (1-1.5): (8-8.2).

4. The method for preparing a multilayer composite drug-loaded nanomotor according to claim 1, characterized in that: In step S1, the temperature of the hydrothermal reaction is 190-210° C., and the reaction time is 9-12 hours.

5. The method for preparing a multilayer composite drug-loaded nanomotor according to claim 1, characterized in that: In step S2, the dosage ratio of the Fe3O4 nanoparticles to ammonia water and ethanol is (3-5):1:(15-22).

6. The method for preparing a multilayer composite drug-loaded nanomotor according to claim 1, characterized in that: In step S2, the surface modifier is tetraethyl orthosilicate, and the mass ratio of tetraethyl orthosilicate to Fe3O4 nanoparticles is (100-120):(22-27); the tetraethyl orthosilicate is added by stirring for 10-30 minutes and then adding half of the tetraethyl orthosilicate, and then adding the other half of the tetraethyl orthosilicate again after an interval of 30-45 minutes.

7. The method for preparing a multilayer composite drug-loaded nanomotor according to claim 1, characterized in that: In step S3, the copper nitrate mixed solution includes copper nitrate, deionized water and ammonia water, wherein the usage ratio of copper nitrate, deionized water and ammonia water is (100-110): (43100-43200): (790-800); the temperature of hydrothermal synthesis is 130-160°C, and the reaction time is 12-14 h.

8. The method for preparing a multilayer composite drug-loaded nanomotor according to claim 1, characterized in that: In step S4, the 3-aminopropyltriethoxysilane used is prepared using an ethanol solution, and the 4-(bromomethyl)phenylboronic acid used is prepared using a methanol solution; in the obtained rtpa / Fe3O4@CuSiO3, the drug loading amount of rt-PA is 10~20 wt.%.

9. The multilayer composite drug-loaded nanomotor prepared by the preparation method according to any one of claims 1 to 8.

10. Use of the multilayer composite drug-loaded nanomotor according to claim 9 in the preparation of drugs for treating arterial thrombosis.